The Admissibility of Using the Provisions of the Polish Civil Code as a Basis for Declaring Resolutions of Meetings of Capital Companies Invalid - Smanio, Ivan (PRAWO i WIĘŹ, 2021)
According to Article 58 § 1 of the Polish Civil Code, a legal transaction contrary to the law and a legal transaction aimed at circumventing the law are different grounds for declaring a legal transaction invalid, whereas according to Article 252§ 1 and Article425§ 1 of the Polish Commercial Companies Code basis for declaring resolutions of the shareholder meeting invalid is only their contradiction with the law. Therefore, the question arises as to whether it is admissible to declare the invalidity of the resolutions of the shareholder meeting which were intended to circumvent the law and whether the resolutions of the shareholder meeting can be qualified as legal actions.A positive answer to the last of the above questions raises further doubts, namely whether the contradiction of the resolutions with the principles of social coexistence referred to in Article 58 § 2 of the Civil Code may also be grounds for declaring the resolutions of the shareholder meeting invalid, and whether it may be stated under Article 58 § 3 of the Civil Code that only a part of the resolutions ofthe shareholder meeting is invalid. The second important issue is the possibility of applying the provisions on defects in the declarations of will referred to in Articles 82-88 of the Civil Code to the votes of shareholders and on their basis to declare the resolutions of the shareholder meeting invalid.Conclusions resulting from the conducted deliberations confirm the possibility of proper application of the provisions of the Civil Code as a basis for declaring the resolutions of the shareholder meeting invalid, with the reservation that when applying these provisions, the nature of individual resolutions of the meetings of capital companies should be taken into account and that the invalidity of these resolutions cannot be declared “by law” ( absolute invalidity), but only as part of an appeal against the resolutions in the mode provided for in the Commercial Companies Code.